PERENCANAAN STRATEGIK KURIKULUM MI DALAM MENINGKATKAN KOMPETENSI LITERASI SISWA DI MIS PAMOYANAN - Dewi, Ratna; Nurlaeli, Leli; Latifah, Aida; Normayunita, Rizki; Handayani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the strategic planning of the curriculum at MIS Pamoyanan in enhancing students’ literacy competence. Using a qualitative descriptive approach with a case study method, data were collected through interviews, observations, documentation, and literature review. The results show that the curriculum planning process involved stakeholders such as school leaders, teachers, and parents, emphasizing the integration of literacy across all subjects. Although implementation efforts such as reading habits and thematic literacy have shown positive impacts—such as improved reading interest and comprehension—the lack of a formal literacy team and structured evaluation system remains a challenge. The study concludes that while the school demonstrates a strong commitment to literacy development, sustainability requires improved organization, consistent execution, and strategic use of resources. Keywords: Strategic Planning, Curriculum Management, Literacy Competence, Madrasah Ibtidaiyah, Primary Education